Building Multicultural Teams: Strategies and Challenges in Cross-Cultural Human Resource Management - Sri Sundari; Zefanus Waruwu; Yulbrin Manurung; Dicky Eka Sanjaya (PT. Pustaka Cendekia Publisher, 2025)
In the era of globalization, organizations are increasingly forming multicultural teams to increase creativity and innovation in the face of the international market. Teams made up of individuals with diverse cultural backgrounds can provide a broader perspective and be responsive to change. However, this diversity also brings challenges, such as differences in communication styles, social norms, and cultural values that can trigger conflicts and misunderstandings. This research aims to identify the challenges faced in building multicultural teams and formulate effective cross-cultural human resource (HR) management strategies. Through a literature review, this study found that the main challenges include differences in communication, cultural conflicts, and biased perceptions. The proposed strategy includes intercultural training, the implementation of inclusion policies, and building an open culture of communication. The conclusion of this study shows that by understanding and managing cultural differences effectively, organizations can improve collaboration and performance of multicultural teams. Recommendations for practitioners include the implementation of intercultural training programs and policies that support diversity, as well as the need for further research to address emerging challenges in managing cross-cultural teams.